Folic acid restricts SARS-CoV-2 invasion by methylating ACE2 - Zhang, Yuanzhou; Pang, Yechun; Xu, Baiyin; Chen, Xingshi; Liang, Shunshun; Hu, Jingying; Luo, Xiaoying (Frontiers in Microbiology, 2022)
The current COVID-19 pandemic is motivating us to elucidate the molecular mechanism of SARS-CoV-2 invasion and find methods for decreasing its transmissibility. We found that SARS-CoV-2 could increase the protein level of ACE2 in mice. Folic acid and MTHFR could promote the methylation of the ACE2 promoter and inhibit ACE2 expression. Folic acid treatment decreased the binding ability of Spike protein, pseudovirus and inactivated authentic SARS-CoV-2 to host cells. Thus, folic acid treatment could decrease SARS-CoV-2 invasion and SARS-CoV-2-neutralizing antibody production in mice. These data suggest that increased intake of folic acid may inhibit ACE2 expression and reduce the transmissibility of SARS-CoV-2, and limitation of folic acid intake to increase ACE2 expression before vaccination may facilitate neutralizing antibody production. Folic acid could play an important role in SARS-CoV-2 infection prevention and control.